If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -7x = 2x + 30 Reorder the terms: 12 + -7x = 30 + 2x Solving 12 + -7x = 30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -7x + -2x = 30 + 2x + -2x Combine like terms: -7x + -2x = -9x 12 + -9x = 30 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -9x = 30 + 0 12 + -9x = 30 Add '-12' to each side of the equation. 12 + -12 + -9x = 30 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = 30 + -12 -9x = 30 + -12 Combine like terms: 30 + -12 = 18 -9x = 18 Divide each side by '-9'. x = -2 Simplifying x = -2
| 7x+33=-28 | | x=11+25 | | 5(6x+7)+1=30x+36 | | 2x-15x=13x-7x-3 | | .04x^2+x-5.24=0 | | x^2+10x+13=2x-2 | | 7x+7=7(x-8) | | 13x-8=-7 | | 7x+7=(x-8) | | 4(x-5)=52 | | -3t+109=-368 | | x^2-15x-6=-7x+3 | | 95=9m+32 | | 95 = 9 m+ 32 | | 4+12=37+x | | 7x+6y=94 | | 11x+19y=17 | | 16w+4x=yforx | | 0.1t+0.9(t-0.2)=2.33 | | -5m=-15 | | 5x-8-3x=16 | | 3a+2a+c+b+2a+3c+5b= | | 12x^2-2x+3c=0 | | z+4=-18 | | z+4= | | 7(16x-25)-6(7x+5)=27x+22-4(x-2) | | X+19=4X+1 | | -a-3(5-4a)=4 | | 0.04a+0.08b=1.2 | | 12x-36x+2=x | | 16t^2+85t-50=0 | | 54=2(x-2)+2(x-(x-5)) |